2010
DOI: 10.1007/s12665-010-0609-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus fractions in the surface sediments of three mangrove systems of southwest coast of India

Abstract: The phosphorus fractions in three tropical mangrove systems of Cochin region were analysed by sequential extraction method. Iron-bound phosphorus was the major fraction in the first two stations, while station 3 was exclusively dominated by calcium-bound phosphorus. Compared to other stations, about tenfold increase in total phosphorus content was observed at station 3. This station is a congregation of communally breeding birds, and there is accumulation of bird guano. Mineralogical analysis showed the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…It was found that P is retained more in the HD mangrove forest soil with a higher concentration of Ca in this site; as the P when combined with Ca is the main mechanism of P retention (Joseph et al, 2011). The content of potential bioavailable P was only 10-20% of the total P in the soil which has also been found for the mangrove soil of the Hun River and Taizi River (Lin et al, 2009).…”
Section: Discussionsupporting
confidence: 56%
“…It was found that P is retained more in the HD mangrove forest soil with a higher concentration of Ca in this site; as the P when combined with Ca is the main mechanism of P retention (Joseph et al, 2011). The content of potential bioavailable P was only 10-20% of the total P in the soil which has also been found for the mangrove soil of the Hun River and Taizi River (Lin et al, 2009).…”
Section: Discussionsupporting
confidence: 56%
“…Generally, organic-bound phosphorus accounts for 6-19% of the TP in coastal sediments (Joseph et al, 2011). In this study, OP was the smallest fraction of all forms of phosphorus, making up about 20% of TP.…”
Section: Discussionmentioning
confidence: 52%
“…This is in general agreement with results from sequential chemical P fractionations which indicated more Ca-associated P within BB sediments and more Fe and/or redox associated P with TA sediments (Section 3.1; Figure 3). Previous studies have used synchrotron XRF coupled with operationally defined chemical P fractionation results to establish the dominant elements governing sediment composition [40][41][42][43][44]. The intensity was calibrated relative to the scattered X-ray (to an intensity of 10000 at 7000 eV), so that the comparison of elemental intensities is possible.…”
Section: Compositional Validation Of Suspended Sediment Using X-ray Fluorescence (Xrf) and X-ray Absorption Near-edge Structure (Xanes)mentioning
confidence: 99%